2020
DOI: 10.1038/s41467-020-18501-w
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase HDA-1 modulates mitochondrial stress response and longevity

Abstract: The ability to detect, respond and adapt to mitochondrial stress ensures the development and survival of organisms. Caenorhabditis elegans responds to mitochondrial stress by activating the mitochondrial unfolded protein response (UPRmt) to buffer the mitochondrial folding environment, rewire the metabolic state, and promote innate immunity and lifespan extension. Here we show that HDA-1, the C. elegans ortholog of mammalian histone deacetylase (HDAC) is required for mitochondrial stress-mediated activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 62 publications
2
66
0
Order By: Relevance
“…The UPR mt can be initiated by either intestinal or neuronal mitochondrial dysfunction [ 445 ]. C. elegans HDAC HDA-1 was also shown to be required for the induction of UPR mt [ 446 ], which further supports a role for decreased histone acetylation in this process. So, low levels of nucleocytoplasmic acetyl-CoA during C. elegans development drive longevity through UPR mt activation, while increased levels or activity of acetyl-CoA synthesis enzymes during adulthood correlates with increased longevity.…”
Section: Decreased Acetyl-coa During C Elegans Development Is Required For the Upr Mt To Increase Lmentioning
confidence: 88%
“…The UPR mt can be initiated by either intestinal or neuronal mitochondrial dysfunction [ 445 ]. C. elegans HDAC HDA-1 was also shown to be required for the induction of UPR mt [ 446 ], which further supports a role for decreased histone acetylation in this process. So, low levels of nucleocytoplasmic acetyl-CoA during C. elegans development drive longevity through UPR mt activation, while increased levels or activity of acetyl-CoA synthesis enzymes during adulthood correlates with increased longevity.…”
Section: Decreased Acetyl-coa During C Elegans Development Is Required For the Upr Mt To Increase Lmentioning
confidence: 88%
“…It was previously shown that the UPR mt regulates innate immunity gene expression to protect the host against infection ( Amin et al, 2020 ; Jeong et al, 2017 ; Mahmud et al, 2020 ; Pellegrino et al, 2014 ; Shao et al, 2020 ). The cnc-4 gene is transcriptionally induced during mitochondrial stress as part of the UPR mt protective pathway, however the exact mechanism for this UPR mt -mediated cnc-4 induction is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that increased mitochondrial ROS activates multiple redox-sensitive kinases, including AMPK and the Mitogen-activated protein kinases (MAPK p38) [26], c-Jun N-terminal kinase (JNK) [27], and extracellular signalregulated kinases (ERK1/2) [28], which regulate mitochondrial biogenesis and mitohormesis modulation through PGC1-a [25]. Phosphorylated PGC-1a by redox-sensitive kinases modulates numerous muscle-related transcriptional factors through nuclear respiratory factors 1 and 2 (NRF-1 and NRF-2) [29], cAMP Response Element-Binding Protein (CREB) [30], Histone deacetylase 1 (HDAC1) [31], mitochondrial transcription factor A (mtTFA) [32], and myocyte enhancer factor-2 (MEF2) [33], including improving muscle metabolism and enhancing muscle performance. PGC1-a also regulates mitochondrial metabolism and biogenesis by activating mitochondrial transcriptional genes such as mitofusin 1/2 (Mfn1/2), cytochrome C, cytochrome oxidase, and various genes involved in the tricarboxylic acid cycle and oxidative phosphorylation process [34].…”
Section: Mitochondrial Adaptation To Exercise and Training: Mitohormesismentioning
confidence: 99%